Identifying Challenges of Covering the Universal Health Insurance Program and Analyzing in SWOT Model - saeid khayatmoghadam; Hamid Erfanian Khanzadeh; Ameneh Zabihi; Ali Asghar Zabihi (Patient Safety and Quality Improvement Journal, 2023)
Introduction:This research aimed to identify the challenges of the universal health insurance coverage program in population, cost, and service dimensions and to provide appropriate strategies to achieve this goal based on the SWOT model in the General Department of Health Insurance of North Khorasan. Materials and Methods: In this research, by using the Delphi method, the opinions of 43 experts about the strengths and weaknesses, opportunities and threats of the universal health insurance coverage program were collected through interviews and the first questionnaire, and with the help of the second questionnaire, the ranking and importance of each factor were determined. Using the SWOT method, appropriate strategies were compiled. Results:The investigations collected ten strengths, eight weaknesses, ten opportunities, and eight threats. The analysis of these factors led to the codification of eight strategies in the ST region, four in the SO region, four in the WO region, and four in the WT region, and the determination of ten main challenges. Conclusion: According to the calculations, the organization’s strategy was placed in the ST area, and the challenges were collected by checking weaknesses and threats. North Khorasan Health Insurance General Administration’s strategy was formulated using strengths to eliminate or reduce threats or homogenous diversity strategy and create diversity in services, and finally, solutions were proposed.